Emotional Intelligence in the Formation of Children's Character - Ibnu Sina; Muhammad Asyam; Suparmi (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
Emotional intelligence (EQ) is an individual's ability to recognize, understand and manage emotions, which plays an important role in forming a child's character. This research focuses on how emotional intelligence influences the formation of children's character, especially in the context of family, educational and social environments. The aim of this research is to understand the factors that support the development of children's emotional intelligence and how EQ contributes to the formation of positive characters, such as responsibility, discipline and social abilities.  The method used in this research is a literature review method, in which various scientific journals, books and articles related to EQ and children's character development are explained in depth. The research results show that emotional intelligence developed from an early age can help children deal with emotional stress and build healthy social relationships.